2009
DOI: 10.1002/app.30185
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the mechanical performances of ternary nylon 6/SEBS elastomer/nano‐SiO2 hybrid composites with controlled morphology

Abstract: ABSTRACT:The distribution of maleated styrene-hydrogenated butadiene-styrene (mSEBS) elastomer and nanoSiO 2 in nylon 6 matrix was controlled by varying the blending procedure. Nano-SiO 2 particles with different surface properties (hydrophilic versus hydrophobic) were adopted to adjust their interactions with other components. Two different structures, separate dispersion of nano-SiO 2 and elastomer particles as well as encapsulation of nano-SiO 2 fillers by the elastomer, were obtained. The structures were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 101 publications
1
7
0
Order By: Relevance
“…On one hand, the presence of nanostructures with a high surface area even at a low concentration results in enhancement of the interphase contact between solid surface and elastomer, and thus has a strong impact on the reinforcing effect. On the other hand, not only in this study but also in the literature, an increase in the mechanical properties has been observed with the addition of SiO 2 nanoparticles [ 36 ]. Additionally, it should be noted that even though the tensile strength of the nanocomposites increased even at higher content of nanofillers (5 wt.%), the values of the elongation at break decreased.…”
Section: Resultssupporting
confidence: 71%
“…On one hand, the presence of nanostructures with a high surface area even at a low concentration results in enhancement of the interphase contact between solid surface and elastomer, and thus has a strong impact on the reinforcing effect. On the other hand, not only in this study but also in the literature, an increase in the mechanical properties has been observed with the addition of SiO 2 nanoparticles [ 36 ]. Additionally, it should be noted that even though the tensile strength of the nanocomposites increased even at higher content of nanofillers (5 wt.%), the values of the elongation at break decreased.…”
Section: Resultssupporting
confidence: 71%
“…As shown in Table 3, the PA 6 composites had a slightly lower degree of crystallinity compared with the pure PA 6. Zhang et al [40] also showed that X c of PA 6 decreased slightly when the PA 6 was filled with Styrene-Ethylene-Butylene-Styrene (SEBS) elastomer and colloidal silica with a particle size of about 10-20 nm. One possible explanation of the lower crystallinity in the composites is the inability of polymer chains to be fully incorporated into growing crystalline lamellae.…”
Section: Mechanical Propertiesmentioning
confidence: 93%
“…Among the numerous reported examples of inorganic/organic hybrid nanoparticles, silica/polymer hybrid nanoparticles have been extensively studied [18][19][20][21]. Despite the increasing studies on silica/polymer hybrid nanoparticles, they all have the specific applications owing to the hydrophobic property of the polymers deposited on the silica surface, such as polystyrene [22,23], poly (methyl methacrylate) [24][25][26], and so on.…”
Section: Introductionmentioning
confidence: 99%